Age determination of Horse Trail peat core from Wales - Jones, Miriam C (PANGAEA, 2021)
14C and 210Pb age determination of a high-resolution peat core from the Past Global Changes - Carbon in Peat on EArth through Time (PAGES_C-PEAT) Project.
Keywords: C-PEAT; Peatland